The interplay of Patched, Smoothened and cholesterol in Hedgehog signaling. (December 2019) - Hu, Ao; Song, Bao-Liang
Abstract : The Hedgehog (HH) pathway plays a pivotal role in regulating a diverse array of events from embryonic tissue patterning to adult organ self-renewal. Aberrant activation of the pathway is linked to carcinogenesis. Key factors in the HH pathway include the signaling ligand HH, the receptor Patched (PTCH), and the G-protein-coupled receptor-like transducer Smoothened (SMO). A long-lasting question about this pathway is how PTCH prevents SMO from being activated. Recent high-resolution structural studies provide insight into the molecular basis of HH recognition by PTCH. Moreover, cholesterol stands out as the endogenous ligand of SMO and acts by binding and/or covalently linking to SMO. In this review, we discuss current advances in HH signaling, the interplay of PTCH, SMO and cholesterol, and propose putative models of SMO activation by cholesterol binding and/or modification.